Unusually young age distribution of primary hepatic leiomyosarcoma: case series and review of the adult literature - Shamseddine, Achraf (BioMed Central, 2010)
BACKGROUND: Primary hepatic leiomyosarcoma is a rare disease diagnosed in older aged adults with a median age of 58 and occasionally in children with a history of immunosuppression. METHODS: From 1998 to 2009, 215 patients were diagnosed with primary hepatic malignancies at our institution, 4 of which were diagnosed with primary hepatic sarcoma (1.8%). Three cases were primary hepatic leiomyosarcomas (LMS) and one case was primary undifferentiated embryonal sarcoma of the liver; median age 30 (range 20-39) years. RESULTS: One patient is currently 12 months post-resection with no evidence of recurrence. Two patients passed away at 19 days and 22 months from small for size liver and tumor recurrence respectively. CONCLUSION: We have presented 3 cases of primary hepatic leiomyosarcoma diagnosed at our institution with an unusually young age distribution and no evidence of immunosuppression. These cases highlight the diagnostic and therapeutic challenges of this rare tumour.